Aplikasi Duolingo dalam Peningkatan Kosakata Bahasa Jerman - Sri Wahyuni; Wahyu Kurniati Asri; Burhanuddin Burhanuddin (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. The purpose of this study was to determine the mastery of German vocabulary in class X MIPA SMA Negeri 8 Makassar through the Duolingo application. The type of research used is Classroom Action Research which consists of two cycles, namely cycle I and cycle II. The subjects in this study were students of class X MIPA SMA Negeri 8 Makassar, totaling 36 people. Data analysis techniques in this study consisted of qualitative and quantitative. Qualitative data was obtained through observation, while quantitative data was obtained through vocabulary improvement tests in cycle I and cycle II. The results of the German vocabulary mastery test showed that the average score in the first cycle was 78.80% and the second cycle was 89.61%. The results of this study indicate that the application of the Duolingo application can increase the German vocabulary of class X MIPA students at SMA Negeri 8 Makassar. Keywords: Improved, Vocabulary, Duolingo App